TSSC4 is a component of U5 snRNP that promotes tri-snRNP formation - Klimešová, Klára; Vojáčková, Jitka; Radivojević, Nenad; Vandermoere, Franck; Bertrand, Edouard; Verheggen, Celine; Staněk, David (Nature communications, 2021)
U5 snRNP is a complex particle essential for RNA splicing. U5 snRNPs undergo intricate biogenesis that ensures that only a fully mature particle assembles into a splicing competent U4/U6•U5 tri-snRNP and enters the splicing reaction. During splicing, U5 snRNP is substantially rearranged and leaves as a U5/PRPF19 post-splicing particle, which requires re-generation before the next round of splicing. Here, we show that a previously uncharacterized protein TSSC4 is a component of U5 snRNP that promotes tri-snRNP formation. We provide evidence that TSSC4 associates with U5 snRNP chaperones, U5 snRNP and the U5/PRPF19 particle. Specifically, TSSC4 interacts with U5-specific proteins PRPF8, EFTUD2 and SNRNP200. We also identified TSSC4 domains critical for the interaction with U5 snRNP and the PRPF19 complex, as well as for TSSC4 function in tri-snRNP assembly. TSSC4 emerges as a specific chaperone that acts in U5 snRNP de novo biogenesis as well as post-splicing recycling. The correct assembly and recycling of the multicomponent spliceosome remains largely elusive. Here, the authors show that a previously uncharacterized protein TSSC4 associates with de novo formed spliceosomal U5 snRNP as well as with a post-splicing U5-PRPF19 particle, and that TSSC4 is important for assembly of the splicing competent tri-snRNP.